Congenital Pulmonary Airway Malformation Type II and Challenge in the decision-making process in developing countries-a case report - Livrinova, Vesna; Komina, Selim; Kostadinova Kunovska, Slavica; Sima, Aneta; Aliji, Nurie; Veljanoski, Darko (Creative Commons Attribution License, MSD Publications, 2024)
Congenital Pulmonary Airway Malformation (CPAM) is a congenital lung disease that can be present from prenatal to childhood. The overall incidence of CPAM is reported to be 1 in 10,000 to 1 in 35,000 births, making it the most common type of congenital lung lesion. This malformation results from the interruption of lung development during various stages of embryogenesis. This case report aims to illustrate the disease through ultrasound imaging, emphasize its characteristics, and discuss parental counseling and decision-making regarding the continuation of pregnancy. It is important to highlight the limitations of prenatal diagnostic precision in developing countries and the need for additional diagnostic tools to improve parental decision-making options
Data from large population registries suggest an incidence of congenital lung cysts ranging from 1 in 8,300 to 1 in 35,000 live births. Large-cyst subtypes account for approximately 70% of CPAM cases or 2 to 8 per 100,000 live births. Type II lesions comprise 15 to 20% of CPAM cases. Although lesion puncture during pregnancy and postnatal surgical excision are recommended treatments, in developing countries, parents may, unfortunately, choose to terminate the pregnancy due to limited diagnostic and treatment options.
Keywords: CPAM; parental; decision